The Role of Autonomy, Competence and Relatednes in Efforts to Increase Student Involvement in Face-to-Face Learning Post-COVID 19; Perspective of Self Determination Theory - Marlina Siregar; Hidayatul Majidah; Riana Sitio; Tetty Rahmiati Harahap (PT ARRUS Intelektual Indonesia, 2022)
The COVID-19 pandemic has forcibly changed the mode of teaching and learning from face-to-face only to online in higher education in Indonesia, which is a new experience and practice for many teachers and students. At the end of 2021, four ministries namely the Minister of Education and Culture, Minister of Religion, Minister of Health, and Minister of Home Affairs of the Republic of Indonesia stated that learning in tertiary institutions starting from the odd semester of the 2021/2022 academic year will be held with limited face-to-face learning while still implementing the health protocol. Online learning that has been running from 2019 to 2021 has certainly changed students' habits in dealing with the learning process. The transition from online to face-to-face learning has the potential to cause problems, especially in the context of students in areas that are still constrained by signals. Online learning within a period of two years with inadequate internet conditions of course greatly affected the minimal involvement of students in learning activities which then triggered the next problem, namely decreased student motivation due to learning conditions that were not conducive during the COVID-19 pandemic. The joint decision of the four ministers to carry out limited face-to-face learning is a breath of fresh air in the world of education to improve the quality of teaching and learning in the university environment, especially on campuses in the regions. The purpose of this study was to determine the effect of student motivation and involvement in increasing student involvement so that they are active in face-to-face teaching and learning activities in Post-COVID 19, especially on regional campuses. The research method used is a survey method with a quantitative research approach. The survey method is considered appropriate because of the large number of research samples. The data used is primary data sourced from respondents' answers to the given questionnaire. The data analysis technique in this study used Partial Least Square (PLS). This technique was used because this study used a large sample size and the relationship between several variables. The results of this study are expected to be able to provide input to campuses in the regions in order to increase student involvement and activeness in learning and teaching activities after COVID 19.